Change of government's subsidization policy improves smoking cessation services: a cross-sectional study from the perspectives of physicians. (December 2016) - Wu, Tai-Yin; Hung, Ling-Yu; Chie, Wei-Chu; Chiu, Tai-Yuan; Guo, Fei-Ran
Abstract Background The Taiwanese government increased financial subsidies for smoking cessation services in 2012. We aimed to evaluate the effects of this new policy on smoking cessation services from the physician's perspective. Methods This was a cross-sectional nationwide survey. Physicians who provided smoking cessation services for more than ten patient encounters in the preceding year of the new policy (February 2011 to March 2012) were recruited. The questionnaire was developed by two experts and was validated by a committee consisting of 11 delegates. Results We sent a total of 1, 319 questionnaires. The response rate was 45.9 %. The majority of respondents were male (88.4 %), middle-aged (65.3 %), and worked as family physicians (56.1 %). Most physicians agreed that the new policy had increased the number of patients seeking smoking cessation, increased patients' willingness to adopt pharmacotherapy, helped physicians to prescribe medications, improved patients' adherence to medications, and improved quality of care. These changes were most prominent in medical centers. Changes in the practice of the 5As (ask, advise, assess, assist, arrange) were moderate. Among different medical settings, the most significant change was an increase in the expenditure on smoking cessation medications. Conclusions The new subsidization policy in Taiwan has improved smoking cessation services. Overall, physicians reported positive effects of the new policy. Further study is warranted to evaluate the long-term influence of the policy.